KONSEP ALIRAN HUKUM KRITIS KAITANNYA DENGAN OMNIBUS LAW UU CIPTA KERJA: KAJIAN FILSAFAT HUKUM - Dairani, Dairani; Ibad, Syahrul (Fakultas Ilmu Sosial dan Humaniora, 2022)
The Critical Legal Studies movement is a movement by academics who choose the leftist school, then this critical legal school is developed by legal practitioners. The birth of Critical Legal Studies was based on dissatisfaction with legal theory and practice in the 1970s. Some people view Critical Legal Studies not as a school of legal thought but only as a movement in legal thought. This is different from other legal schools or schools of law such as Natural Law Schools, Legal Positivism, Utilitarianism, Historical Schools, Sociological Jurisprudence, Legal Realism, and Freirechtslehre. The focus of the study in this article is related to history, the concept of critical legal thought in relation to Legal Positivism and Legal Realism, in this article the author also includes figures from Critical Legal Studies and finally the author tries to relate the views of Critical Legal Studies to the Law. Job Creation with the Omnisbus Law Concept. Conceptual theories and historical approaches as well as legislation are chosen as analytical tools in answering the problems being studied in this article.